Variables related to Physical Exercise in Cancer Patients and Survivors - Marta Victoria Santiago; Mireia Peláez; Josep Alemany; Susana Pulgar (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Cancer constitutes a significant global contributor to morbidity and mortality, inducing adverse effects that impact individuals both during and after treatment. Noteworthy among these effects are depression, anxiety, fatigue, and diminished quality of life. This study aims to ascertain the association between quality of life, fatigue, depression, and anxiety variables and engagement in physical exercise within a cohort of cancer patients and survivors affiliated with the Spanish Association Against Cancer of Cantabria. Additionally, the investigation seeks to identify barriers contributing to physical inactivity in this demographic. Employing a descriptive research design, this study endeavours to illuminate the interplay between these factors in the specified population. A survey was conducted to assess variables such as physical exercise levels, quality of life, fatigue, depression, anxiety, and barriers to physical activity. The findings indicated correlations between physical exercise and depression (p=0.002), anxiety (p< 0.001), fatigue (p< 0.001), and quality of life (p< 0.001) in both cancer patients and survivors. Similarly, survivors exhibited associations between physical exercise and depression (p<0.001), anxiety (p<0.001), fatigue (p<0.001), and quality of life (p<0.001). Conversely, patients and survivors demonstrated significant differences in individual (p<0.001), interpersonal (p=0.002), community-institutional (p=0.001), and time-obligations (p=0.002) barriers. The outcomes affirm the impact of physical exercise on depression, anxiety, fatigue, and quality of life among both cancer patients and survivors, while also elucidating the barriers that rationalize physical inactivity within this demographic.